LINGUISTIC INTERPRETATION OF GENDER STEREOTYPES IN UZBEK PHRASEOLOGY UNDER DIGITALIZATION (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This study examines the representation of gender stereotypes in Uzbek phraseological expressions from a multifaceted linguistic perspective, focusing on their semantic organization, cultural foundations, and mechanisms of development. The research seeks to determine how masculine and feminine images are conceptualized within phraseological units, to identify their evaluative and expressive meanings, and to clarify their role in shaping social identity. The article applies linguocultural, cognitive, semantic, and discourse-based analytical methods. The findings indicate that gender stereotypes embedded in Uzbek phraseology have been formed through long-standing historical and cultural traditions, functioning as linguistic models that reinforce conventional gender roles. In addition, the study reveals that ongoing social and technological changes are contributing to the semantic evolution and reinterpretation of certain stereotypical expressions.
Keywords: gender, stereotype, phraseology, linguoculturology, cognitive model, discourse, connotation, semantic field, social identity, patriarchal paradigm.